PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP TAX AVOIDANCE PADA PERUSAHAAN SEKTOR ENERGI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Rifna Ayu Novita Putri; Nuraisyiah Nuraisyiah; Azwar Anwar (UNIVERSITAS DHARMAWANGSA, 2026)
Tax serves as the primary pillar of state revenue, yet tax avoidance practices in the global and domestic energy sectors remain a serious challenge to fiscal sustainability due to significant profit management incentives. This research aims to analyze the effect of Corporate Social Responsibility (CSR) disclosure on tax avoidance with profitability as a control variable. The scientific approach employed is a quantitative method using multiple linear regression analysis, utilizing secondary data from 32 energy sector companies listed on the Indonesia Stock Exchange during the 2023–2024 period. The results indicate that CSR disclosure (CSRDi) has no significant effect on tax avoidance (Sig. 0.292), implying that social transparency in this sector is merely a form of regulatory compliance and an effort to maintain public legitimacy rather than a tool to conceal tax avoidance. Conversely, profitability (ROA) was found to have a significant positive effect (Sig. < 0.001), concluding that corporate tax decisions are more dominantly influenced by financial performance for fiscal efficiency rather than social commitments. These findings provide a basis for regulators to strengthen tax supervision based on corporate financial performance analysis.